O papel das tecnologias de informação e comunicação no processo ensino-aprendizagem: um estudo do ensino superior nas modalidades presencial e a distância - Silva, Rovilson Dias (2012)
This study aimed to determine the role of the use of information and communication technologies in the process of teaching and learning in undergraduate courses of technology in the area of applied social sciences offered in the traditional modality, presence, and distance education. To achieve this goal we carried out a qualitative research conducted through a case study. The theoretical studies were on issues that lead the researcher to understand the issue and contribute to the field. The following topics were highlighted in the theoretical research: education; superior courses of technology: investigating their regulations and scopes; teaching and learning process: investigating the main theories and strategies and existing courses in Information Technology and Communication: with special emphasis on education oriented. The empirical research was conducted through a case study in a course in an Institution of superior education, in the metropolitan area of Sao Paulo, which offers courses of technology in the area of applied social sciences, among others, Marketing, Logistics, Human Resources, and Management Processes. Data was collected through interviews, with semi-structured questionnaire, and the strategies used for analysis were the Narrative and Content Analysis. For an understanding of the subject, teachers and students were interviewed in two modalities: presence and distance education. We carried out 28 face to face interviews, which were conducted by the researcher, in the Metropolitan Area of Sao Paulo and were later transcribed for analysis. As a result, we obtained among others, that there is a convergence of actions implemented in distance education for the presence education as an increased use of information technologies and communication. These have an important role since the strategy for development of a lecture until student’s feedback.